Predictive potential of angiopoietin-2 in a mCRC subpopulation treated with vanucizumab in the McCAVE trial - Ferreira, Cláudia S.; Babitzki, Galina; Klaman, Irina; Krieter, Oliver; Lechner, Katharina; Bendell, Johanna; Vega Harring, Suzana; Heil, Florian (Frontiers in Oncology, 2023)
Introduction: Angiopoetin-2 (Ang-2) is a key mediator of tumour angiogenesis. When upregulated it is associated with tumour progression and poor prognosis. Anti-vascular endothelial growth factor (VEGF) therapy has been widely used in the treatment of metastatic colorectal cancer (mCRC). The potential benefit of combined inhibition of Ang-2 and VEGF-A in previously untreated patients with mCRC was evaluated in the phase II McCAVE study (NCT02141295), assessing vanucizumab vs. bevacizumab (VEGF-A inhibitor), both in combination with mFOLFOX-6 (modiﬁed folinic acid (leucovorin), ﬂuorouracil (5-FU) and oxaliplatin) chemotherapy. To date, there are no known predictors of outcome of anti-angiogenic treatment in patients with mCRC. In this exploratory analysis, we investigate potential predictive biomarkers in baseline samples from McCAVE participants. Methods: Tumour tissue samples underwent immunohistochemistry staining for different biomarkers, including Ang-2. Biomarker densities were scored on the tissue images using dedicated machine learning algorithms. Ang-2 levels were additionally assessed in plasma. Patients were stratified by KRAS mutation status determined using next generation sequencing (NGS). Median progression-free survival (PFS) for each treatment group by biomarker and KRAS mutation was estimated using Kaplan-Meier plots. PFS hazard ratios (and 95% confidence intervals) were compared using Cox regression. Results: Overall low tissue baseline levels of Ang-2 were associated with longer PFS, especially in patients with wild-type KRAS status. In addition, our analysis identified a new subgroup of patients with KRAS wild-type mCRC and high levels of Ang-2 in whom vanucizumab/mFOLFOX-6 prolonged PFS significantly (log-rank p=0.01) by ~5.5 months versus bevacizumab/mFOLFOX-6. Similar findings were seen in plasma samples. Discussion: This analysis demonstrates that additional Ang-2 inhibition provided by vanucizumab shows a greater effect than single VEGF-A inhibition in this subpopulation. These data suggest that Ang-2 may be both a prognostic biomarker in mCRC and a predictive biomarker for vanucizumab in KRAS wild-type mCRC. Thus, this evidence can potentially support the establishment of more tailored treatment approaches for patients with mCRC.